An introduction to the Longitudinal Surveys of Australian Youth (LSAY). (25th January 2019) - Moore, John; Semo, Ronnie
Abstract : The Longitudinal Surveys of Australian Youth (LSAY) is a large, nationally representative study that follows youth cohorts for ten years at a time as they transition from school into further study, work and other destinations. With more than 20 years of unit record data, LSAY provides researchers with information for six cohorts of Australian youth, offering insight into the pathways of young people across multiple generations. This well-established study programme provides rich information across areas of school and post-school education, employment, household characteristics and key demographics. LSAY data sets are provided free of charge and supported by a dedicated website containing user guides, technical papers and interactive online summary data tools. This study profile introduces readers to LSAY by providing a brief history of its origin and establishment, before examining its design, data collection methods and survey outputs.